1989
DOI: 10.1161/01.cir.79.5.1137
|View full text |Cite
|
Sign up to set email alerts
|

Can superoxide dismutase alter myocardial infarct size?

Abstract: superoxide was xanthine oxidase.17 Supportive evidence from other laboratories19-23 led to experimental attempts to reduce ischemic and reperfusion injury in animal models of myocardial infarction. In several studies, the addition of catalase was not felt to be necessary in vivo because of the presence of significant amounts in erythrocytes. Myocardial Infarct Size: Independent VariablesTo test the hypothesis that SOD will reduce infarct size in an animal model, all other significant independent variables must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(17 citation statements)
references
References 44 publications
0
15
1
1
Order By: Relevance
“…72 Neutrophils may be a source of free radicals during reperfusion injury. Lucchesi and colleagues73 have suggested that leukocytes influence infarct size by the production of free radicals.…”
Section: Effiects Of Free Radical Scavengersmentioning
confidence: 99%
“…72 Neutrophils may be a source of free radicals during reperfusion injury. Lucchesi and colleagues73 have suggested that leukocytes influence infarct size by the production of free radicals.…”
Section: Effiects Of Free Radical Scavengersmentioning
confidence: 99%
“…Reperfusion is associated with polymorphonuclear leukocyte (PMN) accumulation, a burst of oxygen free radical production, activation of inflammation, excessive calcium entry, and possibly late cell death; however, the exact mechanisms whereby free radicals, calcium entry, or inflammation might result in lethal injury are not well defined (5)(6)(7)(8)(9)(10)(11)(12). Studies using superoxide dismutase and other antioxidants have provided interesting leads, suggesting that the oxidative stress and burst of free radical production associated with reperfusion are important mediators of myocardial damage; however, no clear answers have emerged (13). In animal models the net benefit of timely flow restoration outweighs the combination of ischemic and reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…20 The biochemical parameters measured were chosen to reflect different aspects of IRI: GSH as an important tissue antioxidant, which is depleted when free radical production increases; MPO as an index of neutrophil infiltration, neutrophils (MPO) being one of the sources of free radicals in postischemic tissue; and ATP as an index of the energetic state of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, chemotactic factors are released continuously during reperfusion and stimulate neutrophils to enter the injured tissue and act as a source of superoxide for much longer than the tissue halflife of SOD (<30 min). 20,35 In support of this hypothesis, Ricci et al, 32 examining the effects of SOD administration in a canine compartment syndrome model, demonstrated decreased technetium pyrophosphate uptake after 1 hr of reperfusion, but found no effect on muscle function after 17 hr reperfusion.…”
Section: Superoxide Dismutase and Catalasementioning
confidence: 96%
See 1 more Smart Citation